2021
DOI: 10.51791/njap.v48i4.2997
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 and associated lockdown on livestock and poultry sector in Nigeria

Abstract: The COVID-19 pandemic and the associated lockdown for a long period have created a significant adverse impact on different sectors, including that of the agriculture and other allied sub- sectors in Nigeria. The present research was aimed at depicting the impact of this pandemic and the lock down on the poultry sectors in the Nigeria, which has been one of the fastest growing sectors in recent years. Inadequacy of country-wide information has been a major problem for having a thorough understanding of the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The NPR value in the VBT treatment is lower than the other treatments; presumably, this was due to the presence of other secondary metabolite residues that inhibited the absorption and utilization of protein for the growth of VBT-treated rats. Similar results were also obtained in a study by Akure et al [15], where high doses of velvet beans did not increase the growth rate as well as lower doses. On the other hand, the use of 31% velvet bean combined with 69% soybean was able to improve the quality value of protein in velvet bean tempe.…”
Section: Analysis Of Protein Quality Based On Growth Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…The NPR value in the VBT treatment is lower than the other treatments; presumably, this was due to the presence of other secondary metabolite residues that inhibited the absorption and utilization of protein for the growth of VBT-treated rats. Similar results were also obtained in a study by Akure et al [15], where high doses of velvet beans did not increase the growth rate as well as lower doses. On the other hand, the use of 31% velvet bean combined with 69% soybean was able to improve the quality value of protein in velvet bean tempe.…”
Section: Analysis Of Protein Quality Based On Growth Methodssupporting
confidence: 90%
“…Meanwhile, the growth rate of the VBT treatment is significantly lower than the SBT and VB-SBT treatments. It can occur due to less than optimal feed utilization, as well as due to low digestible carbohydrates that limit the availability of digestible nutrients [15]. Previous research conducted by Prayudani et al [17] stated that pre-treatment, such as dehulling, soaking, boiling, and steaming velvet beans, caused changes in digestible carbohydrate levels that varied between 30-48.37%.…”
Section: Analysis Of Protein Quality Based On Growth Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our study, a global media analysis concluded that COVID-19 mitigation measures, including lockdowns and movement restrictions, disrupted the PDN more than the SARS-CoV-2 virus itself [25]. The poultry market in countries like Bangladesh, Morocco, Nigeria, China, and Myanmar also reported incurred losses due to COVID-19-associated lockdowns [26][27][28][29][30]. In Bangladesh, along with rumors, the pre-existing structural factors, such as volatility of input and production prices and credit-dependence, exacerbated the adverse impact of the COVID-19associated lockdown on PDN [26].…”
Section: Discussionsupporting
confidence: 78%
“…In Myanmar, COVID-19 hit the poultry market badly, resulting in the temporary or permanent closure of many broiler farms [29]. Similar to other countries, poultry industries in Myanmar and Nigeria also suffered due to low cash flow, the high cost of feed, and a decline in demand for poultry products [29,30].…”
Section: Discussionmentioning
confidence: 99%